Macrocyclic Cu(II)-organophosphonate building block with room temperature magnetic ordering - Bulut, A.; Zorlu, Y.; Topkaya, R.; Aktas, B.; Dogan, S.; Kurt, H.; Yucesan, G. (ROYAL SOC CHEMISTRY, 2015)
Engineering a copper coordination sphere with organoimine ligands and tuning the organophosphonate protonation states produced[{Cu(2,2'-bpy)}(2)(HO3P(CH2)(8)PO3H2)(4)] (1) and [{Cu(terpy)}(2)-(2,7-FDA-H-2)(2)]center dot(2,7-FDA-H-4)(2H(2)O) (2) (2,7-FDA-H-4 = 2,7-fluore-nonediphosphonic acid) macrocyclic copper-organophosphonate building blocks. 1 exhibits high temperature magnetic ordering, while 2 is paramagnetic. The structures were characterized by single crystal X-ray diffraction.
Keywords: LIGAND-EXCHANGE; POLYMERS; MOFS; Chemistry